MicroRNA Regulation of Peritoneal Cavity Homeostasis in Peritoneal Dialysis. (1st October 2015) - Lopez-Anton, Melisa; Bowen, Timothy; Jenkins, Robert H.
Abstract : Preservation of peritoneal cavity homeostasis and peritoneal membrane function is critical for long-term peritoneal dialysis (PD) treatment. Several microRNAs (miRNAs) have been implicated in the regulation of key molecular pathways driving peritoneal membrane alterations leading to PD failure. miRNAs regulate the expression of the majority of protein coding genes in the human genome, thereby affecting most biochemical pathways implicated in cellular homeostasis. In this review, we report published findings on miRNAs and PD therapy, with emphasis on evidence for changes in peritoneal miRNA expression during long-term PD treatment. Recent work indicates that PD effluent- (PDE-) derived cells change their miRNA expression throughout the course of PD therapy, contributing to the loss of peritoneal cavity homeostasis and peritoneal membrane function. Changes in miRNA expression profiles will alter regulation of key molecular pathways, with the potential to cause profound effects on peritoneal cavity homeostasis during PD treatment. However, research to date has mainly adopted a literature-based miRNA-candidate methodology drawing conclusions from modest numbers of patient-derived samples. Therefore, the study of miRNA expression during PD therapy remains a promising field of research to understand the mechanisms involved in basic peritoneal cell homeostasis and PD failure.